Analysis of Tryout Test Item for Students of the Elementary School Teacher Professional Education Program - Titis Angga Rini; Yuniawatika (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2026)
Abstract: This research is motivated by the importance of the availability of valid and reliable test instruments in measuring the four main competencies of elementary school teachers, which include professional, pedagogical, personality, and social competencies according to educational professionalism standards in Indonesia. The purpose of this study is to analyze the quality of the competency test tryout instrument in the elementary teacher professional education program (PPG SD) through tests of differentiation, difficulty, validity, reliability, and effectiveness of the diverter, so that the feasibility of the question items used can be determined. The research method used a quantitative approach with the analysis of question items on 35 test items, including the validity test, the reliability of Cronbach's Alpha, as well as the analysis of the distribution of answers and the effectiveness of the trickster. The results of the study showed that some of the questions had sufficient quality with adequate differentiation, moderate difficulty, and a well-functioning distractor, but still many invalid items and ineffective deceptionists were found. The reliability value of the instrument was around 0.7, indicating a fairly good internal consistency, although there were still items with low correlations that needed to be revised. Thus, this test instrument has the potential to be used as a competency measurement tool for students of the PPG SD Program, but requires a thorough revision of several items to be more valid, reliable, and representative. Abstrak: Penelitian ini dilatarbelakangi oleh pentingnya ketersediaan instrumen tes yang valid dan reliabel dalam mengukur empat kompetensi utama guru sekolah dasar, yaitu kompetensi profesional, pedagogis, kepribadian, dan sosial sesuai dengan standar profesi pendidikan di Indonesia. Tujuan penelitian ini adalah untuk menganalisis kualitas instrumen uji coba tes kompetensi dalam program pendidikan profesional guru sekolah dasar (PPG SD) melalui pengujian diferensiasi, tingkat kesulitan, validitas, reliabilitas, dan efektivitas distraktor, sehingga kelayakan butir-butir soal yang digunakan dapat ditentukan. Metode penelitian ini menggunakan pendekatan kuantitatif dengan analisis terhadap 35 butir soal, termasuk pengujian validitas, reliabilitas dengan Cronbach’s Alpha, serta analisis distribusi jawaban dan efektivitas distraktor. Hasil penelitian menunjukkan bahwa beberapa soal memiliki kualitas yang memadai dengan tingkat daya pembeda yang cukup, tingkat kesulitan sedang, dan pilihan jawaban pengecoh yang berfungsi dengan baik, namun masih ditemukan banyak item yang tidak valid dan pilihan jawaban pengecoh yang tidak efektif. Nilai reliabilitas instrumen tersebut sekitar 0,7, yang menunjukkan konsistensi internal yang cukup baik, meskipun masih terdapat item dengan korelasi rendah yang perlu direvisi. Dengan demikian, instrumen tes ini berpotensi digunakan sebagai alat pengukuran kompetensi bagi mahasiswa Program PPG SD, namun memerlukan revisi menyeluruh terhadap beberapa butir soal agar lebih valid, reliabel, dan representatif.